A Systematic Review of Studies on Genotoxicity and Related Biomarkers in Populations Exposed to Pesticides in Mexico - Juana Sánchez-Alarcón (MDPI AG, 2021)
In agricultural activities, pest control is essential, and the most effective method is the use of chemical agents that also represent an important source of exposure to potentially toxic compounds. Pesticides constitute a heterogeneous group of compounds designed specifically to control different pests. Besides measuring their levels or that of their metabolites in air, plasma, serum, blood, urine, etc., some studies reported increased DNA damage levels after occupational or environmental pesticides exposure, evidenced by several cytogenetic biomarkers such as chromosomal aberrations (CA), sister chromatid exchanges (SCE), micronuclei frequency (MN) together with other nuclear abnormalities (NA), alkaline comet assay, but also changes in oxidative stress parameters and miRNA levels. Single or combined, these techniques have also been used in genotoxic biomonitoring studies of workers occupationally exposed to pesticides in Mexico. Despite being a country with great agricultural activity and reported excessive pesticide use, genotoxic studies have been relatively few and, in some cases, contradictory. A review was made of the studies available (published until the end of 2020 on PubMed, Web of Science, Redalyc and Scielo, both in English and Spanish) in the scientific literature that evaluated occupational exposure of human samples to pesticides assessed with DNA damage and related biomarkers in Mexico.